Strategi Kepemimpinan Kepala Madrasah dalam Mewujudkan Mutu di Insan Cendekia Halmahera Barat Maluku Utara - Buyung Ismu Tawary (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2021)
This research is based on the establishment of MAN Insan Cendekia in 2017, with all the achievements that Madrasahs have as a measure of quality. The purpose of this research is to find out how the leadership strategy of Insan Cendekia Halmahera Barat madrasah in realizing the quality of madrasah. This research is a descriptive qualitative research, with a phenomenological approach that occurs in the field. Collecting data using observation, in-depth interviews and documentation. The data analysis technique used three lines of analysis, namely data reduction, data presentation and ferification. The results of this study indicate that: The strategy of implementing and evaluating the quality of education in the West Halmahera Intellectuals is carried out in three ways: first: provision of adequate facilities and infrastructure, second: increasing teacher competence and third: developing student potential in the field of science and technology and IMTAQ as a program flagship madrasa. The full support of the central government and local governments for the development of madrasah is a supporting factor in realizing quality. The results obtained from improving the quality of education are the increase in the construction of madrasa facilities, and student achievements obtained from competitions in the field of Science and technology and and MAN Insan Cendekia West Halmahera accredited A in 2018 with a total score of 92.